SYNERGISTIC EFFECT OF BACILLUS MUCILAGINOSUS AND PSEUDOMONAS FLUORESCENS ON THE AVAILABILITY OF SOIL POTASSIUM, GROWTH AND YIELD OF CUCURBITA PEPO L. - Maysoon A. K.,; Kareem. U. Hassan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out at the field of Agricultural Research and Experiments Station during the season 2021-2022 in order to study the  synergestic  effect and compatible between  Bacillus mucilaginosus and  Pseudomonas fluorescens when they added as combination on  potassium availability in the soil and on some plant growth characteristics and yield of Cucurbita pepo L. The experiment included four treatments B0, control , B1 addition of Bacillus mucilaginosus inoculum, B2 addition Pseudomonas fluorescens inoculum and B1 B2 addition of acombination of B1 and B2 inoculum .  The experiment was conducted by using randomised  complete blocks design in three replicates . The results showed that the co- inoculation with Bacillus mucilaginous and Pseudomonas fluorescens significant effect on quantity of  soluble,exchangeable potassium as well as the plant height, dry weight of shoots, percentage of potassium in the shoot and in the fruits and total yield  as compared with individual inoculation for any bacteria B1 or B2 which refers to positive synergestic  effect. B1B2 treatment achieved the highest mean of soluble, exchangeable potassium which amounted to(0.163,0.856) cmol kg-1 soil respectively with an increase of (21.642 %, 15.676%) and (33.606%, 22.636%) of what was achieved by treatment (B1, B2) for the mean of soluble, exchangeable potassium respectively . B1B2 treatment achieved the lowest mean of( non-exchangeable and mineral) potassium which amounted to (35.280)  cmol kg-1 soil.